2011
DOI: 10.1002/mrm.22945
|View full text |Cite
|
Sign up to set email alerts
|

Use of respiratory biofeedback and CLAWS for increased navigator efficiency for imaging the thoracic aorta

Abstract: A novel technique to guide a subjects' breathing pattern using a respiratory biofeedback (rBF) “game” to improve respiratory efficiency is presented. The continuously adaptive windowing strategy, a fully automatic and highly efficient free-breathing navigator gated technique, is used to acquire the data as it ensures that all potential navigator acceptance windows are possible. This enables the rBF to be fully adaptable to a subject's respiratory pattern. Images of the thoracic aorta acquired using balanced st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
2
14
1
Order By: Relevance
“…Feedback of the diaphragm position during CMR has been shown to improve navigator efficiency in adults [5, 6]. This study explored how the use of a feedback game (FG) affects navigator efficiency compared to traditional no-feedback (NF) acquisitions in children .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Feedback of the diaphragm position during CMR has been shown to improve navigator efficiency in adults [5, 6]. This study explored how the use of a feedback game (FG) affects navigator efficiency compared to traditional no-feedback (NF) acquisitions in children .…”
Section: Discussionmentioning
confidence: 99%
“…Previous CMR studies have reported that NF navigator efficiencies can vary from 20 to 45 % in adults [47], and we found a comparable NF navigator efficiency of 33 % in children using a conservative dual-navigator acceptance strategy. Visual feedback of the diaphragm position has been shown to improve end-expiratory navigator efficiency from 45 to 56 % [6] and from 42 to 71 % with the addition of supplemental oxygen [5] leading to a 20 % and 41 % reduction in the number of required heartbeats, respectively. With the use of the FG, we found a slightly better improvement of navigator efficiency from 33 to 58 % in children without the use of supplemental oxygen.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations